The power of coarse graining in biomolecular simulations. (27th August 2013) - Ingólfsson, Helgi I.; Lopez, Cesar A.; Uusitalo, Jaakko J.; de Jong, Djurre H.; Gopal, Srinivasa M.; Periole, Xavier; Marrink, Siewert J.
Abstract : Abstract : Computational modeling of biological systems is challenging because of the multitude of spatial and temporal scales involved. Replacing atomistic detail with lower resolution, coarse grained (CG), beads has opened the way to simulate large‐scale biomolecular processes on time scales inaccessible to all‐atom models. We provide an overview of some of the more popular CG models used in biomolecular applications to date, focusing on models that retain chemical specificity. A few state‐of‐the‐art examples of protein folding, membrane protein gating and self‐assembly, DNA hybridization, and modeling of carbohydrate fibers are used to illustrate the power and diversity of current CG modeling. This article is categorized under: Molecular and Statistical Mechanics > Molecular Dynamics and Monte-Carlo Methods